Handling Brand Crisis through Digital Public Relations: The Case of Esteh Indonesia - Verry Agusta (Jobmark: Journal of Branding and Marketing Communication, 2022)
Esteh Indonesia, a rapidly growing tea outlet brand, faced a severe digital crisis when a consumer complaint went viral on TikTok, garnering more than 1.5 million views and threatening the brand’s reputation. This study aims to analyze how Esteh Indonesia managed the brand crisis through digital public relations strategies to restore consumer trust and brand image. Using a qualitative case study approach, data were collected from documentation of viral content, official corporate statements, and online media coverage, and then analyzed thematically with Benoit’s Image Restoration Theory and the Social-Mediated Crisis Communication framework. The findings reveal that Esteh Indonesia employed a combination of strategies (public apology, corrective action, mediation with consumers, and the recruitment of a celebrity figure as CEO and spokesperson) that successfully mitigated the crisis and revitalized brand perception. The emphasis on swift response created a sense of reassurance and control, which was crucial for calming public concern. Practically, this study highlights the importance of rapid, transparent, and multivocal digital PR interventions in crisis management, fostering feelings of safety and confidence among the audience.